Assessing Unified Payments Interface (UPI) adoption and usage through the interplay of UTAUT factors - K Padma Kiran; Naga Sailaja Vedala (Humanities & Social Sciences Communications)
Abstract The advent of digitization of financial transactions has positioned the Unified Payments Interface (UPI) as a transformative, paperless and cashless digital payment system for consumers in India. Its user-friendly design, robust security features, and broad adoption across small businesses, roadside vendors, and unorganized sectors have established its dominance in facilitating daily digital payments in the Indian market. Over recent years, UPI usage has experienced exponential growth across India. This study examines the factors influencing the intention to adopt UPI with a focus on add-on services, perceived promotional benefits, and perceived trust with the integration of the Unified Theory of Acceptance and Use of Technology (UTAUT). Employing the survey responses of 416 UPI users, this research applies partial least squares structural equation modeling (PLS-SEM) to validate the hypothesized model developed for this study. The findings revealed that facilitating conditions, performance expectancy, effort expectancy, social influence, perceived promotional benefits, and perceived trust significantly influence the users’ intention to adopt UPI, which further influences its usage behavior. Interestingly, add-on services by UPI did not affect the intention of users to adopt UPI, questioning its role in UPI adoption. However, add-on services had a significant impact on performance expectancy and effort expectancy. Additionally, perceived promotional benefits impacted facilitating conditions for UPI usage. Demographic attributes further moderated these relationships: age and occupation significantly moderated the impact of performance expectancy on the intention to adopt UPI, while gender and income did not exhibit any profound moderating effects. The findings offer valuable insights for service providers and policymakers aiming to improve UPI adoption among consumers. Customized strategies considering demographic variations can optimize the platform’s accessibility and appeal to a broader audience.